KAJIAN ESTETIKA DALAM ADAPTASI GAYA KAMASAN PADA FILM ANIMASI I EMPAS TEKEN I ANGSA - Adi Sudi Anggara, I Gede; Gede Arimbawa, I Made (Narada : Jurnal Desain dan Seni, 2024)
This study examines the visual aesthetics in the adaptation of the Kamasan style in the animated film I Empas teken I Angsa. This animated film aims to bring to life the classic painting art from Kamasan Village, Klungkung, Bali, while retaining the distinctive decorative elements of the style. Using a qualitative method, this research is conducted through an in-depth observation of design elements, design principles, and design fundamentals within the animation. The analysis reveals how harmony, contrast, rhythm, gradation, as well as the fundamentals of unity, balance, simplicity, emphasis, and proportion are applied to create a visual composition consistent with the Kamasan style. The results show that the adaptation of the Kamasan style in this animated film successfully preserves traditional aesthetic values while remaining relevant to a modern audience. This film serves not only as entertainment but also as an effective medium for cultural preservation.